The Impact of cDNA Normalization on Long-Read Sequencing of a Complex Transcriptome - Hoang, Nam V.; Furtado, Agnelo; Perlo, Virginie; Botha, Frederik C.; Henry, Robert J. (Frontiers in Genetics, 2019)
Normalization of cDNA is widely used to improve the coverage of rare transcripts in analysis of transcriptomes employing next-generation sequencing. Recently, long-read technology has been emerging as a powerful tool for sequencing and construction of transcriptomes, especially for complex genomes containing highly similar transcripts and transcript-spliced isoforms. Here, we analyzed the transcriptome of sugarcane, with a highly polyploidy plant genome, by PacBio isoform sequencing (Iso-Seq) of two different cDNA library preparations, with and without a normalization step. The results demonstrated that, while the two libraries included many of the same transcripts, many longer transcripts were removed and many new generally shorter transcripts were detected by normalization. For the same input cDNA and the same data yield, the normalized library recovered more total transcript isoforms, number of predicted gene families and orthologous groups, resulting in a higher representation for the sugarcane transcriptome, compared to the non-normalized library. The non-normalized library, on the other hand, included a wider transcript length range with more longer transcripts above ~1.25 kb, more transcript isoforms per gene family and gene ontology terms per transcript. A large proportion of the unique transcripts comprising ~52% of the normalized library were expressed at a lower level than the unique transcripts from the non-normalized library, across three tissue types tested including leaf, stalk and root. About 83% of the total 5,348 predicted long noncoding transcripts was derived from the normalized library, of which ~80% was derived from the lowly expressed fraction. Functional annotation of the unique transcripts suggested that each library enriched different functional transcript fractions. This demonstrated the complementation of the two approaches in obtaining a complete transcriptome of a complex genome at the sequencing depth used in this study.